Fruit-feeding butterflies assemblage in Deciduous Seasonal Forest fragments and grassland - Fleck, Marciane Danniela; Costa, Ervandil Corrêa (Comunicata Scientiae, 2019)
This study aims to investigate the diversity and richness of fruit-feeding butterflies in two fragments of Deciduous Seasonal Forest, with different anthropic explorations, comparing the border and interior environments, and an anthropic area with predominance of grassland, in Taquaruçu do Sul, Rio Grande do Sul, Brazil. Samplings were conducted fortnightly, from August 2012 to July 2013. In each area, were installed attractive traps with a fermented banana and sugarcane juice. In the fragments were installed four traps on the border and four traps 40 meters from the border and in the cultivated pasture area, four traps were also installed. A total of 2,077 specimens of fruit-feeding butterflies were collected, distributed in 45 species and four subfamilies of the Nymphalidae family. The diversity and richness of the fruit-feeding butterflies were higher in the forest fragments. The quantitative cluster analysis segregated the environments into distinct groups, aggregating border environments. By the qualitative analysis there is greater similarity between the fragments. It is concluded that the composition of the fruit-feeding butterflies species is different among the studied areas, and the environments of the forest fragments have similar diversity and richness among them, while the cultivated grassland area is less richness and diversity.